â€œBELI INDONESIAâ€ MOVEMENT AS BREAKTHROUGH TO MANAGE THE PEOPLE'S ECONOMY IN THE MIDDLE OF LEGAL DEADLOCK IN INDONESIA - Trenggono, Heppy (UNISSULA, 2022)
Beli Indonesia can be said to be a political movement, when viewed from a simple political understanding. Politics builds perceptions in order to gain power. The